The Influence of Parenting Patterns on Early Childhood Social Development - Anggi Nursahara; Haliatun Nisa; Risnaeni Ainunsyah (Penerbit Hellow Pustaka, 2024)
Social emotional aspects in early childhood are very important to develop from an early age. The importance of parenting patterns to introduce social-emotional influences greatly influences children's ability to interact with their environment. The aim of this research is to study literature and libraries regarding the influence of parenting styles on the social emotional development of early childhood. As well as being a reference for parents and prospective parents to find out the best parenting style in providing child care. This research uses a literature study type of research by collecting data through various theoretical references that are relevant to the cases or problems found. Based on the results of this research, it shows that the parenting style that best suits children's social and emotional development is a democratic parenting style where children have the freedom to do things but are still responsible. Because democratic parenting gives children the opportunity and freedom to choose.